2014
DOI: 10.1175/mwr-d-14-00101.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Infrared, Microwave, and Radio Occultation Satellite Observations on Operational Numerical Weather Prediction

Abstract: A comparison of the impact of infrared (IR), microwave (MW), and radio occultation (RO) observations on NCEP's operational global forecast model over the month of March 2013 is presented. Analyses and forecasts with only IR, MW, and RO observations are compared with analyses and forecasts with no satellite data and with each other. Overall, the patterns of the impact of the different satellite systems are similar, with the MW observations producing the largest impact on the analyses and RO producing the smalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Using sensitivity techniques from the adjoint method, the authors pointed out that GPSRO provides 10% of the 24-h forecast error reduction together with the Infrared Atmospheric Sounding Interferometer (IASI) and Atmospheric Infrared Sounder (AIRS). Cucurull and Anthes [10] confirmed the role of GPSRO data as an anchor observation, reducing the global forecast bias. A more effective use of satellite radiances was produced and a greater number of these observations passed through quality control procedures by assimilating GPSRO data.…”
Section: Introductionmentioning
confidence: 74%
“…Using sensitivity techniques from the adjoint method, the authors pointed out that GPSRO provides 10% of the 24-h forecast error reduction together with the Infrared Atmospheric Sounding Interferometer (IASI) and Atmospheric Infrared Sounder (AIRS). Cucurull and Anthes [10] confirmed the role of GPSRO data as an anchor observation, reducing the global forecast bias. A more effective use of satellite radiances was produced and a greater number of these observations passed through quality control procedures by assimilating GPSRO data.…”
Section: Introductionmentioning
confidence: 74%
“…The selection of wind observations is very important in the prediction of near-surface winds because such winds are strongly affected by terrain features, land surface processes, turbulence and the stability of the PBL. Although the assimilation of satellite observations can lead to better predictions of atmospheric profiles, many studies have shown that the assimilation of conventional observations alone can be more effective in the prediction of near-surface winds (Stauffer and Seaman 1991;Zapotocny et al 2008;Cucurull and Anthes 2014;Zhang and Wang 2014;Zhang et al 2015). The selection and configuration of data assimilation schemes will have a large impact on the prediction of near-surface winds.…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of infrared and microwave measurements generally have different and distinct impacts on tropospheric weather prediction models [25]. As noted by Zou et al (2013) [26], more valuable information within and below clouds can be obtained when using microwave radiance technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave radiation can penetrate non-precipitation clouds as well as carrying atmospheric humidity information within the cloud, as compared to infrared humidity sensors which do not give this information. In NWP systems, Cucuruul and Anthes (2014) [25] evaluated satellite microwave measurements of the stratosphere. Authors found that they can lead to larger impacts than infrared measurements when assimilated separately in the global operational forecast model in NCEP.…”
Section: Introductionmentioning
confidence: 99%